The socio-economic impact of government's urban renewal initiatives: The case of Alexandra Township - Mbanjwa, Phindile (Department of Civil Engineering, 2018)
The purpose of this research is to investigate the impact of the implementation of the Alexandra Renewal Programme (ARP) on the lives of residents in the Johannesburg township of Alexandra, in South Africa. The urban renewal project was a government initiative in collaboration with the private sector and community-based organisations. The project aimed to improve the physical, social and economic environments of Alexandra, a densely-populated township whose history includes political resistance, poverty, high levels of crime and unemployment, and yet is located adjacent to South Africa's successful commercial capital, Sandton. The impact of urban renewal programmes such as the ARP has not been evaluated along every dimension, nor recently with concerns raised about the pace of government efforts to drive the change required. Hence, the objective of this study was to assess the impact of the Alexandra urban renewal programme on its residents. Alexandra typifies the socio-economic marginalisation of black urban neighbourhoods during the apartheid era. Nearly 500 000 people live in approximately 100 000 households in formal and informal housing; unemployment is estimated at 60%, and most household incomes fall below the extreme poverty line of less than USD1 per person per day. Hence the ARP was designed to boost job creation, promote a healthier environment, through provision of affordable and sustainable services, such as decent housing, roads, water supply, sanitation and other infrastructure, and to reduce crime. The case study was conducted using qualitative research techniques. Focus groups were conducted with 32 residents from formal and informal settlements in the township. Research data was analysed using thematic content analysis. As a former resident of Alexandra with a long family history in the township, the researcher could provide a grounded and corroborative insight into the phenomenon under study. The research findings indicate that the implementation of the ARP programme has been generally consistent with the designed outcomes. The respondents indicated that the programme had some positive impact on improved access to government facilities and services, and on some housing and infrastructure projects. However, the participants also expressed frustration, and indicated that they had not gained significant benefits, especially on job creation and business opportunities. In addition, the residents believed that more could be done on the provision of basic services such as housing, water and sanitation. The effectiveness of government officials responsible for the ARP was also a concern. The study recommends that the three spheres of government (national, provincial and local) should collaborate more to develop relevant policies which drive urgency and effectiveness into the implementation of the urban renewal programme (URP) in Alexandra, and in the Gauteng province in general. The findings of this study contribute to the broader review of URPs in South Africa, and can assist government's developmental structures in evaluating the impact of these and future programmes.